(untitled) (Journal of actual problems of jurisprudence, 2026)
This article offers a critical examination of the foundational assumptions of centralized constitutional review as embodied in the Kelsenian model of constitutional courts. Drawing on the principles of judicial monism and legal realism, it argues that the institutional separation of constitutional adjudication from ordinary judicial functions produces a systemic pathology described as “constitutional atrophy”: the progressive erosion of the constitutional competence of judges of general jurisdiction. Through a comparative analysis of post-Soviet legal systems, with particular emphasis on Kazakhstan and other member states of the Commonwealth of Independent States (CIS), the article demonstrates that concentrated constitutional review operates less as a guarantor of fundamental rights than as a bureaucratic filter insulating the state apparatus from the direct effect of constitutional norms. The study combines doctrinal legal analysis with institutional critique to show how the monopolization of constitutional interpretation by specialized tribunals undermines the principle of iura novit curia and creates structural conditions for the capture of the judiciary by the executive branch. It further contends that the diffuse model of constitutional review, developed in the United States following the landmark decision in Marbury v. Madison (1803), provides more effective protection of individual rights by distributing the authority to interpret the constitution throughout the entire judicial hierarchy. The article concludes by proposing a roadmap for institutional transformation in CIS jurisdictions, advocating the abolition of constitutional courts and the integration of constitutional review functions into unified supreme judicial bodies, thereby restoring the constitutional competence of every judge and democratizing access to constitutional justice. Keywords: Constitutional courts, Kelsenian model, judicial monism, diffuse review, constitutional atrophy, post-Soviet legal systems, judicial review, CIS, Kazakhstan, negative legislator, erga omnes, inter partes, iura novit curia, stare decisis.